PENGARUH RASIO AKTIVITAS DAN RASIO LEVERAGE TERHADAP PROFITABILTAS APOTEK XYZ - Liska Marlindasari; Dickta Oktaviani (Jurnal Farmasi IKIFA, 2023)
Profitability is a ratio to assess a company's ability to make a profit or profit. This research is a study on the analysis of financial statements at Apotek Xyz located in the Cigugur District, Kuningan Regency to determine the Effect of Activity Ratio and Leverage Ratio on Xyz Pharmacy. This type of research is quantitative research with descriptive and verifiable methods. The sempel retrieval technique is carried out by purposive sampling. This study uses descriptive statistical test tools, classical assumption test, multiple linear regression analysis test and hypothesis test. The results of the study simultaneously showed that the ratio of activity (total asset trunover) and the ratio of leverage (debt to asset ratio) affect profitability (return on equity), as evidenced by the significance value f of 0.019 while the activity ratio (total asset turnover) has no effect on profitability (return on equity), as evidenced by the significance value t of 0.230 and the leverage ratio (debt to asset ratio) has a positive effect on profitability (return on equity), as evidenced by the significance value of t of 0.035.